The Effectiveness of Diversion Through Restorative Justice For Handling Children In The East Java Police - Setyorini, Erny Herlin; Kongres, Evi; Hailitik, Asri Gresmelian Eurike; Zainulla, Pandu Satriawan (SASI, 2023)
Introduction: Children are the next generation of the nation who must be protected in order to grow up properly. Handling children's cases through the Juvenile Criminal Justice System has devastating impacts on children's futures.Purposes of the Research: This study aims to analyze the effectiveness of handling children's cases through diversion in the East Java Regional Police and analyze obstacles to handling children's cases through diversion so that solutions are found to achieve maximum diversion implementation as mandated by the Children's Criminal Justice System Law.Methods of the Research: This type of research is sociolegal research with a statutory approach, a conceptual approach, and a comparison approach, namely Law Number 11 of 2012 concerning the Juvenile Criminal Justice System.Results of the Research: The results showed that of the five police and police in the East Java Regional Police area, it showed that not 50% of the handling of children's cases had been successfully resolved through diversion. The causative factors include the non-achievement of the consent of the victim's child and his family. Therefore, the condition of consent of the victim's child and his family in Article 9 paragraph (2) must be abolished because Article 7 paragraph (2) of Law Number 11 of 2012 does not require the consent of the victim's child and his family. In practice is the main obstacle to achieving diversion, should be eliminated in the best interest of the child in accordance with the principles of the Convention on the Rights of the Child.